Correlates of perceived favorability of online courses for quantitative versus qualitative undergraduate business majors. Issue 8 (16th November 2016) - Blau, Gary; Pred, Robert; Drennan, Rob B.; Kapanjie, Darin
ABSTRACT: An online survey tested the association among background, technological, and course-related variables with perceived favorability of online courses for two independent samples of fall 2015 and spring 2016 business undergraduates taking at least one online or hybrid course. Results showed that perceived learning was a consistent positive correlate of perceived favorability of online courses for quantitative majors, whereas number of prior online or hybrid courses and perceived ease of technology tool use were consistent positive correlates for qualitative majors.